Malnutrition case in patient with pulmonary tuberculosis through a family medicine approach - Priscilla Elnatan Christina; Sherren Tanzia; Muhammad Akbar Nasution; Silviana Tirtasari (Institute of Computer Science (IOCS), 2023)
Underweight is a body mass index less than 18.5 kg/m2. The prevalence of underweight in Southeast Asia from 1969 to 2017 was around 20%. The percentage of underweight in Indonesia reached 5% whilst in Banten Province in 2017 was 5.4%. Around 18,45% patients and 32,19% of patients with tuberculosis at Cikupa Health Care were underweight from January to September 2022. Mrs SH is an underweight patient with pulmonary tuberculosis. Her weight has not shown any improvement despite almost completing the intensive phase treatment of pulmonary tuberculosis. Improvement in nutritional status and monitor the pulmonary tuberculosis therapy in Mrs SH. Mrs SH, 24 years old, came to Cikupa Health Center to control her pulmonary tuberculosis treatment. The patient known to have nutritional problems since her childhood. Her weight has not shown any improvement despite almost completing the intensive phase of pulmonary tuberculosis treatment. After a family medicine approach for 5 weeks, the patient's weight has increased from 34.7 to 37.1 kg. The patient has also been notified for regular treatment and promised to follow pulmonary tuberculosis treatment until it is complete. The family medicine approach has been able to increase the patient's weight even though the target weight has not been achieved. The patient also promised to follow pulmonary tuberculosis treatment until it is complete. It is hoped that by following all the interventions given, the patient's body weight can reach the ideal weight and be declared complete of pulmonary tuberculosis treatment.